2014
DOI: 10.1155/2014/435481
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Reversal of Diabetes by All-Trans Retinoid Acid and Exendin-4 in NOD Mice

Abstract: It has been shown that all-trans retinoid acid (ATRA) hinders the development of autoimmune diabetes by inducing immune tolerance status. Meanwhile, exendin-4 increases beta-cell function and mass. Thus, we hypothesized that ATRA and exendin-4 combination therapy would prevent and reverse autoimmune diabetes. NOD/scid mice were intravenously transferred with splenocytes isolated from 12-week-old female NOD mice. After adoptive transfer, mice were treated with vehicle, ATRA (0.5 mg/mouse intraperitoneally every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
(17 reference statements)
1
12
0
Order By: Relevance
“…These findings indicated that ATRA protects against glomerular and tubule-epithelial hypertrophy in initial changes of DN without affecting elevation of blood glucose levels. These results are consistent with previous evidences of nephroprotective role of ATRA [13,14,15,16,17,18,35].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings indicated that ATRA protects against glomerular and tubule-epithelial hypertrophy in initial changes of DN without affecting elevation of blood glucose levels. These results are consistent with previous evidences of nephroprotective role of ATRA [13,14,15,16,17,18,35].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have suggested that ATRA might protect against the development of renal pathological changes including DN [13,14,15,16,17]. Nevertheless, whether ATRA might attenuate renal fibrogenesis has not been studied in DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, RA treatment was able to lessen pancreatic destruction through counteracting with the inflammatory niche-induced damage. However, after the initiation of T1D, RA treatment might not be sufficient to reverse hyperglycemia nor improve the survival rates even when combined with exendin-4, a glucagon-like peptide-1 receptor agonist that enhances pancreatic β-cell function [ 90 ]. These findings indicate that disease stage-specific modulation of the immune system with RA and RA therapies could be promising preventions but not cures for T1D.…”
Section: Efficacies Of Ra In the Treatment Of Autoimmune Diseasesmentioning
confidence: 99%
“…Pharmacological administration of RA to non-obese diabetic (NOD) mice, which like BB rats spontaneously develop a T1D phenotype with autoimmune destruction of β cells, delayed the onset and severity of T1D and protected from the loss of β-cell mass[50]. Two studies convincingly demonstrated that RA prevented the immunodestruction of β cells in NOD mice by increasing the numbers of tolerogenic immunosuppressive Treg cells, which suppressed CD4 + and CD8 + T-effector cells[51,52].…”
Section: Vitamin a And Type 1 Diabetesmentioning
confidence: 99%